2018
DOI: 10.3390/w10050604
|View full text |Cite
|
Sign up to set email alerts
|

Performance of National Maps of Watershed Integrity at Watershed Scales

Abstract: Watershed integrity, the capacity of a watershed to support and maintain ecological processes essential to the sustainability of services provided to society, can be influenced by a range of landscape and in-stream factors. Ecological response data from four intensively monitored case study watersheds exhibiting a range of environmental conditions and landscape characteristics across the United States were used to evaluate the performance of a national level Index of Watershed Integrity (IWI) at regional and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…In India, E. coli isolated from the Ganga river showed resistance to antibiotics cephalosporin (37%), ampicillin (20%), amoxicillin (20%), tetracycline (20%), and ciprofloxacin (5.30%) ( Biswas et al, 2015 ). Similarly, several studies had reported the presence of antibiotic-resistant E. coli in different environmental and clinical samples ( Sayah et al, 2005 ; Ram et al, 2007 , 2008 ; Li et al, 2010 ; Tagoe et al, 2011 ; Guo et al, 2014 , 2017 ; Adzitey et al, 2015 ; Chen et al, 2017 ; Muringani, 2017 ; Amer et al, 2018 ; Diwan et al, 2018 ; Igwaran et al, 2018 ; Lu et al, 2018 ; Mishra et al, 2018 ; Mitali et al, 2018 ; Vital et al, 2018 ; Amador et al, 2019 ; Sandhu et al, 2019 ). Study on distribution of ARGs in the present study reflects that the spring water of Sikkim are reservoirs of multiple ARGs.…”
Section: Discussionmentioning
confidence: 90%
“…In India, E. coli isolated from the Ganga river showed resistance to antibiotics cephalosporin (37%), ampicillin (20%), amoxicillin (20%), tetracycline (20%), and ciprofloxacin (5.30%) ( Biswas et al, 2015 ). Similarly, several studies had reported the presence of antibiotic-resistant E. coli in different environmental and clinical samples ( Sayah et al, 2005 ; Ram et al, 2007 , 2008 ; Li et al, 2010 ; Tagoe et al, 2011 ; Guo et al, 2014 , 2017 ; Adzitey et al, 2015 ; Chen et al, 2017 ; Muringani, 2017 ; Amer et al, 2018 ; Diwan et al, 2018 ; Igwaran et al, 2018 ; Lu et al, 2018 ; Mishra et al, 2018 ; Mitali et al, 2018 ; Vital et al, 2018 ; Amador et al, 2019 ; Sandhu et al, 2019 ). Study on distribution of ARGs in the present study reflects that the spring water of Sikkim are reservoirs of multiple ARGs.…”
Section: Discussionmentioning
confidence: 90%
“…We acknowledge that the results of this IWI analysis were not validated with aquatic data as has been done for the conterminous United States IWI analysis (Kuhn et al 2018;Thornbrugh et al 2018;Johnson, Leibowitz, and Hill 2019). Though data do exist for the Matanuska-Susitna basin, these are generally collected opportunistically for project-specific purposes and mostly focus on the Wasilla-Palmer core area.…”
Section: Discussionmentioning
confidence: 92%
“…Integrity, are used to quantify and compare integrity at wholewatershed scale with that of the more local drainage of individual stream segments to assess the scales of stressors in the individual segments (Johnson, Leibowitz, & Hill, 2019;Kuhn et al, 2018;Thornbrugh et al, 2018).…”
Section: Citation Details Resultsmentioning
confidence: 99%